Lecturers’ Feedback on Students’ Reading at Politeknik LP3I Medan - Ramadani Ramadani; Andrysyah Andrysyah; Siska Hasibuan; Asri Sanusi; Doni Efrizah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study dealt lecturers’ feedback on students’ reading at Politeknik LP3I Medan. This study aimed to find out lecturers’ feedback on students’ reading at Politeknik LP3I Medan. This study used the theory from Ellis (2009). Methodology of this study used qualitative research by Miles, Huberman and Saldana (2014), it was interactive method. The collecting data of this study was observation and recording students and lecturers’ utterances on learning process in reading class. The recording was transcribed to find out the data related to the study. The result of this study, there were direct feedback and indirect feedback. There were four process of feedback that implemented in learning process on reading class, they are explicit correction, metalinguistic comment, recast and repetition. Process of feedback was not related to the theory from Ellis (2009). There were six processes of feedback by Ellis (2009). They were explicit correction, metalinguistic comment, recast, repetition, elicitation and clarification request. In this study, researcher did not find two processes of feedback, they were elicitation and clarification request.